Path Analysis: Effect of Gestational Factors, Psychosocial Factors, and Antenatal Class Program on Toddler Growth - Gita Ayu Indria; Bhisma Murti; Yulia Lanti Retno Dewi (Journal of Maternal and Child Health, 2016)
Background: According to David Barker